Dolphin-derived NETosis results in rapid Toxoplasma gondii tachyzoite ensnarement and different phenotypes of NETs. (February 2020) - Imlau, Michelle; Conejeros, Iván; Muñoz-Caro, Tamara; Zhou, Ershun; Gärtner, Ulrich; Ternes, Kerstin; Taubert, Anja; Hermosilla, Carlos
Abstract: Toxoplasma gondii is a cosmopolitan zoonotic parasite and nowadays considered as an emerging neozoan pathogen in the marine environment. Cetacean innate immune reactions against T. gondii stages have not yet been investigated. Thus, T. gondii tachyzoites were utilized to trigger neutrophil extracellular traps (NETs) in bottlenose dolphin ( Tursiops truncatus ) polymorphonuclear neutrophils (PMN). Scanning electron microscopy unveiled T. gondii tachyzoites as potent and rapid inducers of cetacean-derived NETosis. Co-localization of extracellular chromatin with global histones, granulocytic myeloperoxidase and neutrophil elastase confirmed classical characteristics of NETosis. Interestingly, different phenotypes of NETs were induced by tachyzoites resulting in spread, diffuse and aggregated NET formation and moreover, 'anchored' and 'cell free' NETosis was also detected. Current data indicate that cetacean-derived NETosis might represent an early, ancient and well-conserved host innate defense mechanism that not only acts against T. gondii but might also occur in response to other closely related emerging apicomplexan parasites affecting marine cetaceans. Highlights: Dolphin PMN confronted with T. gondii tachyzoites resulted in a rapid release of NETs. NET structures presented classical co-localization of NE, MPO and histones. NETs ocured in different morphological forms: spread NETs ( spr NETs), aggregated NETs ( agg NETs) and diffuse NETs ( diff NETs). Dolphin NETs appeared to be ROS independent.